Endoscopic pancreatic sphincterotomy in patients with IPMN-related recurrent pancreatitis: A single center experience. Issue 1 (January 2023) - Schepis, T.; Tringali, A.; D'aversa, F.; Perri, V.; Familiari, P.; Boškoski, I.; Nista, E.C.; Costamagna, G.
Abstract: Background: Acute recurrent pancreatitis (ARP) is a rare manifestation of Intraductal Papillary Mucinous Neoplasms (IPMN) of the pancreas; ARP is a relative indication for pancreatic surgery in the setting of IPMN. Endoscopic pancreatic sphincterotomy (EPS) has been described as a minimal invasive treatment to reduce the episodes of ARP secondary to mucus migration in IPMN. Methods: patients with IPMN-related ARP treated with ESP from January 2004 to December 2020 were retrospectively selected. Clinical and technical data were recorded. A clinical follow-up (minimum 12 months) was performed to assess the number of episodes of AP occurring after EPS. Results: 25 patients were included. The mean follow-up after ESP was 93.4 months (SD± 56.6). The mean number of AP before and after EPS were respectively 3.29 (SD ± 1.04) and 0.51 (SD ± 0.71). A complete response (no further episodes of AP) and a partial response (>50% reduction of AP episodes) were obtained in 64% and 24% of the cases, respectively, with an overall response rate of 88%. One post-EPS bleeding and one minor-papilla stenosis were reported and were endoscopically managed. Two patients underwent pancreatic resection for the occurrence of high-risk stigmata for cancer progression. Conclusions: EPS is a safe and effective treatment to reduce the number of episodes of AP in selected patients with IPMNs-related ARP. Prospective trials are needed to confirm these data.